YIIFSWA II OPENDAY - Interview with Ibrahim Ogodoma - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Interview with Ibrahim Ogodoma, NAYFP&M from Nassarawa State, Nigeria at YIIFSWA II Open Day. YIIFSWA-II showcases High Ratio Propagation Technologies and demonstrates large scale production of early generation seed yam.